Leo Strauss and the rediscovery of Maimonides - Green, Kenneth Hart, 1953- (University of Chicago Press, 2013)
In Leo Strauss and the Rediscovery of Maimonides, Kenneth Hart Green explores the critical role played by Maimonides in shaping Leo Strauss's thought. In uncovering the esoteric tradition employed in Maimonides's Guide of the Perplexed, Strauss made the radical realization that other ancient and medieval philosophers might be concealing their true thoughts through literary artifice. Maimonides and al-Farabi, he saw, allowed their message to be altered by dogmatic considerations only to the extent required by moral and political imperatives and were in fact avid advocates for enlightenment. Strauss also revealed Maimonides's potential relevance to contemporary concerns, especially his paradoxical conviction that one must confront the conflict between reason and revelation rather than resolve it. An invaluable companion to Green's comprehensive collection of Strauss's writings on Maimonides, this volume shows how Strauss confronted the commonly accepted approaches to the medieval philosopher, resulting in both a new understanding of Maimonides and a new depth and direction for his own thought. It will be welcomed by anyone engaged with the work of either philosopher.